Three signs of an inquisitorial salvation - Rosado Calderón, Juan (Razón y fe, 2023)
In this article, I propose a review of the risks of false salvation, according to three signs represented by the three temptations to Jesus in the desert. In order to do so, I do a philosophical interpretation of the Legend of The Grand Inquisitor by Dostoyevski that will follow the one initiated by the Russian thinker Pavel Evdokimov. On this reading, I propose an idea of philosophy as resistance to three power vectors, which are opposed by the monastic vows of poverty, chastity and obedience, from which it is possible to remain faithful to God’s project for the world (Wisdom).
Keywords: Evdokimov; Dostoevsky; salvation; temptation; power; monasticism; freedom